Electric-magnetic-dielectric synergism and Salisbury screen effect in laminated polymer composites with multiwall carbon nanotube, nickel, and antimony trioxide for enhancing electromagnetic interference shielding. (May 2022) - He, Qian-Ming; Tao, Jun-Ru; Yang, Yi; Yang, Dian; Zhang, Kai; Fei, Bin; Wang, Ming
Graphical abstract: Highlights: Excellent EMI SE was achieved in PDMS-based composites with multiple fillers. The 4:3:3 ratio of MWCNTs, Ni, and Sb2 O3 exhibited high synergism for EMI SE. The synergism became more obvious in the composites with laminated structure. Strong Salisbury screen effect was found in MNS/NS/M and M/NS/M composites. The EMI SE values/A coefficients were ∼ 57.4 dB/∼0.75 in the M/NS/M composites. Abstract: Herein, polydimethylsiloxane (PDMS) was used as matrix, multi-walled carbon nanotubes (MWCNTs), nickel (Ni) and antimony trioxide (Sb2 O3 ) particles were used as multiple fillers to explore the electric-magnetic-dielectric loss synergism in the composites. Generally, MWCNTs and Ni particles in the composites provided mainly electric and magnetic dissipation of microwaves, respectively. Sb2 O3 particles were used to improve impedance matching and reduce surface reflection of microwaves. The synergistic effect of the Sb2 O3 -Ni-MWCNTs on electromagnetic interference (EMI) shielding effectiveness (SE) was discussed for combination of fillers with different ratio. Furthermore, the symmetrical structure (SS) and asymmetric structure (AS) composites were designed to obtain high EMI SE and absorption coefficient. For example, the SS composites and the AS composites could achieve the high EMI SET /absorption coefficient of ∼ 57.4 dB/ ∼ 0.75, and ∼ 55.7 dB/ ∼ 0.80, respectively, because of the electric-magnetic-dielectric synergism and Salisbury screen effect.